Les métamorphoses de l’inimitié - Tristan Quemener; Clément Renault (Ateliers d'Anthropologie)
The Ashéninka report stories of meetings with peyari, a fortuitous event viewed as contact with the dead’s universe of sociability, which is liable to plunge the witness into a state of pathological stupefaction. This article studies the peyari based on its phenomenological and pragmatic existence conditions, taking into account the cannibalistic thought that characterises this group. In the course of an ethnography of the peyari, which shows it to be a tool for objectifying relations of enmity, this contribution outlines a logic of the sensible that seems to promote an intensive practice of politics based on metamorphosis.